Systemic Lupus Erythematosus: Targeted Literature Review of the Epidemiology, Current Treatment, and Disease Burden in the Asia Pacific Region - Tanaka, Yoshiya; O'Neill, Sean; Li, Mengtao; Tsai, I‐Ching; Yang, Ya‐Wen (Arthritis care & research (2010), 2022)
Objective To understand the epidemiology, current treatment, and disease burden of systemic lupus erythematosus (SLE) in the Asia Pacific (APAC) region. Methods A targeted literature review of published evidence on SLE in the APAC region was conducted, using the Medline database (2008–2018), conference proceedings, and other supplementary sources. Results The current review identified 70 studies conducted in China (n = 15), Japan (n = 13), Taiwan (n = 12), Korea (n = 9), Australia (n = 7), Hong Kong (n = 6), Singapore (n = 4), and multiple places within the APAC region (n = 4). Incidence rates (per 100,000 persons per year) ranged from 0.9–8.4, while prevalence rates ranged from 3.7–127 (per 100,000 persons); however, recent data were limited. Asian patients with SLE were reported to have higher disease severity, disease activity (higher SLE disease activity index scores), and organ damage accrual, along with increased morbidity, mortality, and susceptibility to renal involvement compared with other ethnicities in the APAC region. The risk of developing SLE is higher in the Asian population. Routinely used SLE therapies included belimumab, hydroxychloroquine, cyclophosphamide, tacrolimus, azathioprine, mycophenolate mofetil, and glucocorticoids; however, prescribing patterns varied across the region. Increased disease activity was associated with high economic burden and poor quality of life for SLE patients in the APAC region. Conclusion SLE remains a disease with a significant unmet medical need for an innovative therapy that is well‐tolerated and effective for patients in the APAC region. Further evidence is required to better characterize the disease and fully capture the burden and impact of SLE in the APAC region. This review has highlighted where there is a paucity of data from patients across the APAC region.